Adverse Effect on Bacteria of Peritoneal Dialysis Solutions that Contain Acetate. Issue 5673 (27th September 1969) - Richardson, James A.; Borchardt, Kenneth A.
Abstract : Peritoneal dialysis solutions which contained 43 mEq per litre of acetate had a greater antibacterial effect than those containing lactate. Bacteria were isolated from 15 separate clinical infections, each caused by Escherichia coli, Pseudomonas sp., or Staphylo-coccus aureus . Incubation in the dialysate made with acetate substantially reduced the number of viable organisms from all but one of the 45 isolates. It is suggested that solutions made with acetate may provide greater protection from peritonitis.